The future of Russia in the context of analysis of political value orientations (Путеводитель предпринимателя)
Changes in the outlook of the citizens of the country can serve as an important indicator of the reality of social transformation in general. Analyzing and synthesizing these shifts can allow a deeper understanding of the reasons for successes and failures taking place in Russia of institutional reforms, also assess the effectiveness of the transformation of the Russian society, of his mind, and, as a consequence, the values of political culture.